Enzymatic assisted aqueous oil extraction from Jatropha curcas / Hazrati Wazir - Wazir, Hazrati (2013)
Enzymatic assisted aqueous oil extraction (EAAOE) of Jatropha curcas was investigated in this research. The presence of Alcalase® 2.4 L and Celluclast® 1.5 L facilitates the recovery of the oil up to 58%. Parameters involved in EAAOE such as selection and concentration of enzymes, ratio of Jatropha curcas seeds: water (mass/volume), pH, temperature, duration of incubation time, effect of ultrasonication, and oil recovery from oil-water mixture were optimised. The highest oil recovery (58%, m/m) was obtained with 6 mL/1g water/oil, 6% (m/m) enzyme, temperature at 50°C, seed particle size less than 1 mm, pH 5.0 and pH 8.0 for Celluclast® and Alcalase® respectively, incubation for 4 hours (Alcalase®) and 8 hours (Celluclast). In order to enhance oil recovery, centrifugation was conducted at 4°C and 8000 rpm, coupled with hexane-aided separation and subsequent 2 hours freezing of the aqueous layer. The alkaline protease was found to be more efficient than cellulase. In addition, the step-wise addition of enzyme studies was carried out to investigate the sequential enzymatic mechanism on the oil extraction. A comparison between the one-step and step-wise addition of Alcalase® 2.4 L and Celluclast® 1.5 L at the same concentration found that the cellulosic materials were broken down first and followed by protein hydrolysis to facilitate oil releasing and extraction process. The present study had also isolated and elucidated toxic substances, phorbol esters which are responsible for the toxicity of Jatropha curcas to animals and humans, by using high performance liquid chromatography and liquid chromatography - mass spectrometry. The result demonstrated that the phorbol ester content of Jatropha oil extracted by the EAAOE method were 0.2% and 0.3% for enzyme Alcalase® and Celluclast®, respectively. The oil extracted from EAAOE exhibited good physicochemical properties and is useful as a biodiesel feedstock in industrial applications. iii The oil exhibited iodine values of 96.5 and 95.1, peroxide values of 1.83 meq/kg and 1.77 meq/kg, saponification values of 207.9 and 205.1, density values of 0.9130 g/cm3 and 0.9134 g/cm3, moisture content of 0.11% and free fatty acid (FFA) content (% as oleic acid) of 2.15 and 2.30 for enzyme Alcalase® and Celluclast®, respectively. Oleic and linoleic acid were detected as the dominant unsaturated fatty acids which was about 77%, while stearic and palmitic were the highest saturated fatty acids content in Jatropha oil with 23%. Therefore, Jatropha oil can be categorised as oleic–linoleic oil. The favourable method for Jatropha curcas oil with high FFA transesterification was direct esterification of the FFA prior to transesterification reaction. In comparison with double-stage transesterification process, it was found that the former method managed to achieve higher total methyl ester (62.1% m/m), near 30% greater than the latter transesterification method. In addition, acid pre-treatment in esterification has shortened the total reaction duration from 6 hours 30 minutes to 4 hours 50 minutes. The analysis of Jatropha oil methyl ester by this method consist of FFA content of 0.26%, moisture content of 0.043%, density value of 0.8709 g/cm3 at 25°C and pour point of 3°C. Therefore, the findings showed that the quality analysis of Jatropha oil methyl ester was well within the biodiesel specifications, namely, American standard ASTM D6751 and European standard EN 14214.